(3OjhGf GHf MRes - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe GdChMO CHheMeO Ydj Hf CMeO GdCfOdSj GdMeO ddg jGQH hGdTcQ Je dc GdMeO eG HGM HGdTcQ ae s
(3BNQgG (B:s
(3PGc GdPj dSJ COQj eG CbGH````dg Hg ef GdTcQ aj SQi hEYdGfj hCSde hOe dj aj YR haj OYI eG dGM aj GddLI GdNVQGA RLeGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B82 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(16302 (3R(B) s
Keywords: (3GdCOHs